The Effect Polychronicity on Employee Engagement - Tarihoran, Sahat Andalan Juliwan Saputra; Mon, Muhammad Donal; MuchsinatiÂ , Evi Silvana (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
The hotel industry is a work environment where activities are increasingly complex. Rapid world changes and globalization have caused major problems in today's commercial environment, especially in the hospitality industry including the provision and maintenance of superior guest services, labor scarcity, and retention of the best employees. This study examines the role of compensation as a moderating variable to test how polychronicity and job satisfaction influence employee engagement in the hospitality business. Purposive sampling and procedure were employed in the survey method data collection for the quantitive investigation. The study involved 422 hotel employees in Batam. Using Smart-PLS 3 tools, the data was processed and analyzed using the structural equation modeling PLS technique. With the challenges of globalization and growing operational complexity, it is crucial to understand how these factors can impact employee performance and retention in the hospitality sector, which is why this research attempts to provide a thorough understanding of this relationship. The study found that: job satisfaction positively and significantly mediated the relationship between polycrhonicity and employee engagement; polychronicity positively and significantly affected employee engagement; and job satisfaction positively and significantly affected job satisfaction.